The Structure of Yb3+ Aquo Ion and Chloro Complexes in Aqueous Solutions at Up to 500 C and 270 MPa - Mayanovic, Robert A.; Jayanetti, J. K. D. S. (My University, 2002)
We report here on X-ray absorption fine structure (XAFS) measurements used to determine the structure of the Yb3+ ion in aqueous solutions over a range of temperatures from 25 to 500 °C and pressures up to 270 MPa. Fluorescence Yb L3-edge spectra were collected separately from nitrate (0.006m Yb/0.16m HNO3) and chloride (0.006 m YbCl3/0.017 m HCl) aqueous solutions within a hydrothermal diamond anvil cell. The Yb-O distance of the Yb3+ aquo ion in the nitrate solution exhibits a uniform reduction at a rate of 0.02 Å/100 °C, whereas the number of oxygens decreases from 8.3 ( 0.6 to 4.8 ( 0.7, in going from 25 to 500 °C. No evidence for nitrate complexes was found from measurements made on this solution. The Yb3+ is found to persist as an aquo ion up to 150 °C in the chloride aqueous solution. In the 300-500 °C range, chloro complexes are found to occur in the solution, most likely of the type Yb(H2O)ä-nCln +3-n (ä 7). The Yb-Cl distance of the chloro ytterbium(III) complexes is found to decrease uniformly at a rate of about 0.02 Å/100 °C, whereas the number of chlorines increases from 0.5 ( 0.3 to 1.8 ( 0.2 in the 300-500 °C temperature range. Conversely, the Yb-O distance undergoes a lower uniform reduction at a rate of 0.007 Å/100 °C, whereas the number of oxygens decreases from 8.3 ( 0.5 to 5.1 ( 0.3 in going from 25 to 500 °C in the same solution.